Effects of fermentation with Lactobacillus fermentum 21828 on the nutritional characteristics and antioxidant activity of Lentinus edodes liquid. (14th December 2021) - Zhang, Meina; Wang, Xingnan; Wang, Xiaowei; Han, Mengzhen; Li, Hongcai; Yue, Tianli; Wang, Zhouli; Gao, Zhenpeng
Abstract: BACKGROUND: Few studies to date have evaluated the use of Lactobacillus and Bifidobacterium in edible fungus fermentation. To obtain a fermented Lentinus edodes liquid product with good taste and effects, a strain with good fermentation performance from nine strains tested was selected, and the physicochemical properties and antioxidant capacity of the resulting product were evaluated. RESULTS: Lactobacillus fermentum 21828 exhibited adhesion, tolerance to low pH and bile salts, and good fermentation performance. The number of viable bacteria was 1.05 × 10 8 CFU mL −1, and the extraction rate of crude polysaccharide from L. edodes was 2.79% after fermentation. The effects of fermentation on the contents and composition of nutrients in L. edodes liquid were marked, with changes in total soluble protein, total soluble sugar, total acid, and total phenol levels. The 2, 2‐diphenyl‐1‐picrylhydrazyl radical‐scavenging rate in the fermentation liquid was 93.01%, which was significantly higher than that in non‐fermented liquid (80.33%). Furthermore, analysis of volatile and 5′‐nucleotide contents showed that fermentation altered the flavor of the product, whereas sensory evaluation showed that the fermented product was preferred. CONCLUSION: Our study demonstrated that the fermented L. edodes liquid exhibited better nutritional and functional properties, as well as sensory characteristics, compared with unfermented liquid. © 2021 Society of Chemical Industry.